Constructions with the verb EITI ‘to go’ in the 16th century Lithuanian writings - Lisauskaitė, Agnė (Lietuvių kalba, 2020)
This research investigates the semantics and the structure of the constructions with the verb eiti ‘to go’ extracted from the old Lithuanian written texts, dating back to the 16th century. It aims to examine the meanings and the structure of the constructions that contain the motion verb eiti ‘to go’ within their structure. There is a considerable body of research investigating various aspects of motion verbs in different languages of the world, including Lithuanian. However, no studies have so far targeted constructions with the verb eiti ‘to go’, found in the 16th century Lithuanian writings. The present study is based on the qualitative content analysis, quantitative analysis, and frame semantics methodology. The concordances of the Lithuanian texts have been filtered out from the Database of Old Writings digitalised by the Institute of the Lithuanian Language. The examples were taken from Martynas Mažvydas’ Katekizmas (MžK) and Forma krikštymo (MžF), Jonas Bretkūnas’ Biblija (BB), Giesmės Duchaunos (BG), Kancionalas (BKa) and Kolektos (BKo), Mikalojus Daukša’s Katekizmas (DK) and Postilė (DP).The frames of Motion, State, Law, Eternity, Service, Opposition, Law, etc., evoked by the selected constructions, were examined using the frame semantics (FrameNet Project). The research has shown that the current constructions with the motion verb eiti ‘to go’ can form the core of the mentioned frames. The observation that has emerged from this analysis is that some meanings of the analysed constructions are conserved in the current Lithuanian language while others have already disappeared. This work could be useful for historical linguists.
Keywords: frame semantics; motion; old writings; verb